Suppliers' listing status and trade credit provision - Abdulla, Yomna; Dang, Viet Anh; Khurshed, Arif (Journal of Corporate Finance, 2020)
We show that public suppliers extend more trade credit than their private counterparts. The impact of stock market listing on accounts receivable is more pronounced among firms that are financially more constrained or more reliant on external finance. Moreover, firms significantly increase their trade credit provision following equity issuances in stock exchanges. These results are consistent with the argument that stock market listing status improves firms' access to external sources of financing, especially equity capital, thus enhancing their ability to offer more trade credit to customers.